Controle de Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) com milho bt ou inseticidas - Vertuan, Hallison Vernisio (2013)
The fall armyworm, Spodoptera frugiperda, is the main pest on corn and its injuries cause decrease of grain yield. It is an insect extensively studied but with the advent of new technologies such as Bt corn, it is necessary that studies be conducted on this new tactical control, alone or in combination with others insecticides. Experiments were performed in order to evaluate the effectiveness of genetically modified genotypes of corn with bt genes: MON 810 (Cry 1Ab), MON 89034 (Cry1A.105, Cry 2Ab2), MON 89034 × NK603 × TC1507 (Cry 1A.105, Cry 2Ab2, Cry1F) and TC1507 (Cry1F) and insecticides applied as foliar spray (spinosad, lufenuron, methomyl and chlorpyrifos) and seed treatment (imidacloprid + thiodicarb, fipronil and thiamethoxam), in controlling of S. frugiperda. Fields were conducted in Não-Me-Toque, RS, Rolândia, PR, Cachoeira Dourada, MG and Sorriso, MT and laboratory experiment was conducted at FAMV-UPF, Passo Fundo, RS. It was observed that S. frugiperda was efficiently controlled by MON 89034, MON 89034 ×NK603 × TC1507 and TC1507 in four locations. MON 810 also exerted caterpillar control, but was less efficient than the other genetically modified genotypes. Bt corn reduced the injuries of S. frugiperda and Helicoverpa zea in the ear and provided an efficient control of Diatraea saccharalis. Considering the average of the four locations, the grain yield of genotypes MON 89034 and MON 89034 × TC1507 × NK603 was superior than conventional genotype DKB 390 (control). Among the insecticides tested with foliar application, spinosad showed the best efficacy against S. frugiperda, resembling the control provided by MON 810. As a seed treatment, the mixture thiodicarb + imidacloprid was more effective in controlling S. frugiperda compared with thiamethoxam and fipronil, resembling the control afforded by genotype MON 89034 without insecticide, until six days after growth stage V2